If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -5y = 0 Solving 12x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 12x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 12x + 0 = 0 + 5y 12x = 0 + 5y Remove the zero: 12x = 5y Divide each side by '12'. x = 0.4166666667y Simplifying x = 0.4166666667y
| 10x+8=5x+128 | | 89-2x=3x+24 | | 160-7x=20x+19 | | 5x+6=-84-10x | | y=3(5)+23 | | 4x+31=12x-49 | | 7y-12=9 | | 4r+6=22 | | e-15=16 | | 6t=42 | | w-9=5 | | 11x+12=6x+102 | | h+7=15 | | 105-2x=25x+18 | | 12-9x=67-44x | | (n+4)x*4=48 | | 94-2x=43x-19 | | 126-5x=5x+6 | | 6a-6=42 | | 125-3x=5x+21 | | 237-3x=42x+22 | | 3n=12 | | 3x+2=18-5x | | x+8=3+2x | | 5x+13=-39-8x | | 114-2x=9x+18 | | 4x+7y=299 | | 16x-8=6x+42 | | 13x+13=76-4x | | 34-g=25 | | 18x-9=6x+42 | | 9-9x=144-44x |